Radiation stability of iron nanoparticles irradiated with accelerated iron ions; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 354, iss. 1 - Uglov S. R. Sergey Romanovich; Remnev G. E. Gennady Efimovich; Kvasov N. T. Nikolay Trafimovich; Safronov I. V.; Chistjakov S. A. (2015, 2015)
Title screen